CIRI POKOK TINDAKAN SOSIAL DALAM NOVEL MALIOBORO AT MIDNIGHT KARYA SKYSPHIRE: PERSPEKTIF SOSIOLOGI SASTRA - Umah, Mas Rurotul; Abadi, M. Imron; Yanuarsih, Sri (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
Depictions of people's lives not only occur in the real world, but are also found in literary works. One of the literary works that presents stories about life through writing is a novel, such as the novel entitled Malioboro at Midnight by Skysphire. In the novel Malioboro at Midnight by Skysphire, there are activities carried out by the characters, namely social actions. The main characteristics of social action are the target of sociological research. Therefore, this research aims to describe in depth and obtain an objective picture of the main characteristics of social action in the novel Malioboro at Midnight by Skysphire. The research method used is descriptive qualitative. The research approach is a combination of two fields of study, namely literary sociology. The research was carried out through several stages, including data reduction, data presentation, and drawing conclusions. The results obtained in this research are (1) actions that have subjective meaning, namely positive and negative assumptions, (2) actions that are mental and subjective, namely feelings of anger that dominate, (3) actions that have a positive influence, namely the application of social values. which is beneficial to other people and gives inner satisfaction to the perpetrator, (4) the action is directed at other people to get a response, namely rational, instrumental and affective action, and (5) the action is a response, namely affective action. So, it can be concluded that sociological aspects in the form of the main characteristics of social action can be described objectively in literary works.